'If you kill tobacco, you kill Malawi': Structural barriers to tobacco diversification for sustainable development. (3rd August 2020) - Smith, Julia; Fang, Jennifer
Abstract: There is growing recognition that diversifying away from tobacco farming can contribute to progress towards the Sustainable Development Goals in lower‐ and middle‐income countries. However, diversification projects are often limited in scope and impact. This paper analyses structural barriers to tobacco diversification and opportunities to challenge them, based on the perceptions of those engaged in policy processes in Malawi, the most tobacco dependent country in the world. Through analysis of 11 key informant interviews, four structural barriers are identified: perceived economic importance, lack of alternatives, vested industry interests, and the polarised conflict between tobacco control advocates and farmers. Respondents suggest these might be overcome through import substitution, a focus on securing alternative markets, and the inclusion of tobacco farmers in global processes. In ratifying the Framework Convention on Tobacco Control, the Government of Malawi would be able to access diversification support, build a positive relationship with the global tobacco control community and address industry influence.